Genetic characterization of human T-cell lymphotropic virus type 1 in Mozambique: transcontinental lineages drive the HTLV-1 endemic. - Ana Carolina P Vicente (Public Library of Science (PLoS), 2011)
Background Human T-Cell Lymphotropic Virus Type 1 (HTLV-1) is the etiological agent of adult T-cell leukemia (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). It has been estimated that 10-20 million people are infected worldwide, but no successful treatment is available. Recently, the epidemiology of this virus was addressed in blood donors from Maputo, showing rates from 0.9 to 1.2%. However, the origin and impact of HTLV endemic in this population is unknown. Objective To assess the HTLV-1 molecular epidemiology in Mozambique and to investigate their relationship with HTLV-1 lineages circulating worldwide. Methods Blood donors and HIV patients were screened for HTLV antibodies by using enzyme immunoassay, followed by Western Blot. PCR and sequencing of HTLV-1 LTR region were applied and genetic HTLV-1 subtypes were assigned by the neighbor-joining method. The mean genetic distance of Mozambican HTLV-1 lineages among the genetic clusters were determined. Human mitochondrial (mt) DNA analysis was performed and individuals classified in mtDNA haplogroups. Results LTR HTLV-1 analysis demonstrated that all isolates belong to the Transcontinental subgroup of the Cosmopolitan subtype. Mozambican HTLV-1 sequences had a high inter-strain genetic distance, reflecting in three major clusters. One cluster is associated with the South Africa sequences, one is related with Middle East and India strains and the third is a specific Mozambican cluster. Interestingly, 83.3% of HIV/HTLV-1 co-infection was observed in the Mozambican cluster. The human mtDNA haplotypes revealed that all belong to the African macrohaplogroup L with frequencies representatives of the country. Conclusions The Mozambican HTLV-1 genetic diversity detected in this study reveals that although the strains belong to the most prevalent and worldwide distributed Transcontinental subgroup of the Cosmopolitan subtype, there is a high HTLV diversity that could be correlated with at least 3 different HTLV-1 introductions in the country. The significant rate of HTLV-1a/HIV-1C co-infection, particularly in the Mozambican cluster, has important implications for the controls programs of both viruses.